Research on the Ways to Improve the Practical Teaching Ability of Early Childhood Physical Education Teachers in Pre-service Training (Contemporary Education and Teaching Research, 2024)
Early childhood education (ECE) is a critical stage for developing physical fitness, motor skills, and social competence in young children. In recent years, with the growing recognition of the importance of early childhood education, the pre-service training of early childhood physical education teachers has received more attention. Practical teaching ability is a core factor affecting the quality of early childhood physical education teachers' education. To enhance the practical teaching ability of early childhood physical education teachers, this article explores specific strategies and approaches that can be adopted at the pre-service training stage to guide teacher education institutions and policymakers to optimize pre-service training programs and improve the quality and effectiveness of future teachers. The article identifies several key ways to enhance the pre-service training of early childhood physical education teachers: the intensification of theoretical training, the deepening of practical training, the establishment of mechanisms for reflection and evaluation, and the application of technology and innovative methods to enhance teachers' professional knowledge and skills, and also their motivation to teach and their ability to innovate.